(untitled) (Asian Education Studies, 2019)
Over the decades, education is seen as a pedagogical relationship between the teacher and the learner. Traditionally, what a learner needed to learn, what knowledge and skills that should be taught were always decided by a teacher. However, education has transformed and moved from pedagogy to different approaches namely andragogy, heutagogy and peeragogy, the newest approach to education to suit the needs of the society. Therefore, the aim of this paper is to identify primary school teachers’ acceptance of technology and to investigate their readiness towards Heutagogy and Peeragogy. This study also sought to identify possible demographic factors which may influence respondents’ readiness towards Heutagogy and Peeragogy. Data were collected from 48 primary teachers in a primary school in Malaysia using a survey and were analysed using descriptive statistics. The results showed that the in-service teachers have a very positive readiness towards technology in Education as well as using heutagogy approach and peeragogy approach in their teaching. The study about the teachers’ acceptance of technology, readiness towards Heutagogy and Peeragogy and the challenges faced are expected to provide useful information for the educators to provide support for future study.